A business realization of VR panoramic video in smart home - Chuanfei LUO; Dehui KONG; Xiangkai LIU; Ke XU; Hao YANG (Dianxin kexue)
As a new video format,panoramic video has greatly changed the way people watch videos,and can enhance the user experience of the smart home in the video field.Good decoding ability and excellent network support advantages held by IPTV play an active role in the application and promotion of panoramic video.Combined with virtual reality technology,the main characteristics of panoramic video was analyzed.Further more,an IPTV-based service realization scheme was presented in virtue of four key technologies including FOV view adaptive framework,MCTS encoding and multi-resolution,multiple tile video distribution formula and partially decoded tile technique with viewport change in terminal.